TEACHERS’ KNOWLEDGE AND CONFIDENCE IN CONDUCTING ORAL HEALTH ACTIVITIES IN KINDERGARTENS - Syarifah Haizan Sayed Kamar; Ab Halim, Noorhazayti; Md Rashid, Nur Atikah; Muhammad Radzi, Nur A’isyah (International Journal of Allied Health Sciences, 2019)
Teachers play an important role in promoting good oral health practices among preschool children as they are one of the most influential people in a child’s life. This study aims to assess preschool teachers’ oral health knowledge and confidence in conducting oral health promotion activities in kindergartens. A cross-sectional study was conducted among 111 preschool teachers (Government = 60, Private = 51) from selected kindergartens. Stratified random cluster sampling was used to select the participants. Their knowledge and confidence in conducting oral health activities were assessed using self-administered questionnaires. Data were analysed using SPSS Statistics version 23.0. Preschool teachers in Kuantan had moderate oral health knowledge (Mean score 62.6%, SD 19.2%) and high confidence in conducting oral health-related activities (Mean score 77.7%, SD 13.7%) at the kindergartens. Significant relationships were reported between teachers’ oral health knowledge and age (p=0.008), and type of preschool (p<0.01). There was also a significant relationship between a teacher’s confidence and type of preschool (p<0.01). However, there was no significant relationship reported between confidence and teacher’s age (p=0.057). Preschool teachers in Kuantan have high oral health knowledge and confidence in conducting oral health activities. Younger and private teachers were less confident than older and government teachers.